Improvement of the esca index for the evaluation of ecological quality of coralligenous habitat under the european framework directives - PIAZZI, L.; GENNARO, P.; CECCHI, E.; SERENA, F. (Mediterranean Marine Science, 2015)
<!–[if gte mso 9]> Normal 0 14 false false false IT X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The ESCA (Ecological Status of Coralligenous Assemblages) index was recently developed to evaluate the ecological quality of coralligenous habitat. The study aims to improve the first index proposal through testing response to different sources of anthropogenic pressures and optimizing the sampling effort. ESCA was calculated on 14 sites and tested against a gradient of human pressures. Moreover, the main scales of spatial variability of assemblages were evaluated and values of index obtained with different sampling designs were compared. Results showed that studied sites resulted in high, good or moderate ecological status, according to an increasing gradient of the anthropization level. Values of ESCA index obtained with different methods have been compared and photographic method provides EQR values lower than destructive method. Spatial variability of assemblages was higher at large and small scales than at intermediate ones. Two locations for each study site and 20 replicated samples for each location may be consider the best sampling combination providing reliable values of ESCA index for the evaluation of ecological quality of coralligenous assemblages. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>